FIRST RECORD OF Micrasema cinereum Mosely (TRICHOPTERA, BRACHYCENTRIDAE) IN TURKEY AND A LIST OF THE CADDISFLY FAUNA IN ARAÇ CREEK - KÜÇÜKBASMACI, İbrahim; Fındık, Özlem (Galenos Yayinevi, 2019)
Systematic studies on Trichoptera larvae in Turkey are very limited. The larval stage of the endemic species remains especially unknown. This study was carried out in Araç Creek between April and October 2013 and it is the first study to determine the caddisfly fauna in Araç Creek. Fourteen caddisflies taxa belonging to nine genera within eight different families (Brachycentridae, Hydropsychidae, Hydroptilidae, Lepidostomatidae, Leptoceridae, Limnephilidae, Psychomyiidae and Rhyacophilidae) were identified. Four of these taxa have previously been recorded from the creek and the other ten taxa are new records for the study area while Micrasema cinereum Mosely is the first record for the Trichoptera fauna of Turkey. As a result of the study, the number of caddisfly taxa in Turkey is now 501, with the addition of M. cinereum.
Keywords: Hidrobiyoloji; New Record; araç creek; Science (General); Turkey; Description; New record; larvae; description; benthic macroinvertebrates; Araç creek; Turkey; larvae; Arac Creek; Benthic Macroinvertebrates; Q1-390; Larvae; description; turkey; new record; Hydrobiology; benthic macroinvertebrates